The ravine a family, a photograph, a Holocaust massacre revealed - Lower, Wendy 1965- (Houghton Mifflin Harcourt, 2021)
"A single photograph-an exceptionally rare "action shot" documenting the horrific final moment of the murder of a family-drives a riveting process of discovery for a gifted Holocaust scholar"--
Keywords: Geschichte 1941; Judenvernichtung; Myropilʹ; Holocaust, Jewish (1939-1945) / Ukraine / Sources; Jews / Persecutions / Ukraine / Sources; Ukraine / History / German occupation, 1941-1944 / Sources; Germany / Politics and government / 1933-1945 / Sources; World War, 1939-1945 / Atrocities / Ukraine / Sources; Images, Photographic; HISTORY / Asia / General; Atrocities; Jews / Persecutions; Politics and government; Germany; Ukraine; 1933-1945; History; Sources